Phenomenology "wide open" : after the French debate - Janicaud, Dominique, 1937-2002 (Perspectives in continental philosophy, 2005)
"Is phenomenology in jeopardy? Will the phenomenological movement survive intact amongst the ever-expanding adherence to some part of this doctrine? Will phenomenology cease to be a major influence in contemporary continental philosophy and beyond? Are we dealing with a purely and intrinsically French phenomenon in the vast domain of all philosophy? Can some resolution be brought about through the limitation, or de-limitation, of our sphere of investigation? Will we ever succeed in lifting the ambivalence out of the phenomenological project?"